2019
DOI: 10.1080/14763141.2019.1650102
|View full text |Cite
|
Sign up to set email alerts
|

Differences in swimming smoothness between elite and non-elite swimmers

Abstract: The aim of the study was to investigate whether jerk cost (JC) can discriminate between swimming levels. Nine elite and nine non-elite swimmers swam a 50-m front-crawl sprint wearing a 3D accelerometer on their back between the inferior angles of the scapulae. Lap times and JC were calculated from the acceleration signal and compared between groups and between swimmers within a group. The elite swimmers swam significantly faster lap times than the non-elite swimmers (p < 0.001). They did so with significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…After the seventy-four full texts were screened, one was excluded by type [ 50 ], six by exposure [ 51 , 52 , 53 , 54 , 55 , 56 ], seven by outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and one by participant [ 64 ] eligibility criteria. Reference list analysis revealed 31 studies on the topic as potentially meeting the inclusion criteria, with full-text analysis excluding 10 articles by type [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], 2 by exposure [ 75 , 76 ] and 8 by outcomes [ 18 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Seven additional studies from snowballing citation tracking process were deemed eligible for inclusion, and all were included [ 29 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the seventy-four full texts were screened, one was excluded by type [ 50 ], six by exposure [ 51 , 52 , 53 , 54 , 55 , 56 ], seven by outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and one by participant [ 64 ] eligibility criteria. Reference list analysis revealed 31 studies on the topic as potentially meeting the inclusion criteria, with full-text analysis excluding 10 articles by type [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], 2 by exposure [ 75 , 76 ] and 8 by outcomes [ 18 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Seven additional studies from snowballing citation tracking process were deemed eligible for inclusion, and all were included [ 29 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…26,27 In the remaining sections (S15-25 m, S25-35 m, S35-45 m, and S45-50 m), the literature reports significant differences in swimming speed during the 50 m freestyle competition between elite and non-elite swimmers. 28 However, there is no information about swimmers within the same competitive level or at least a more homogeneous group. Our data show that such difference in swimming speed was maintained along the race.…”
Section: Mean Data Comparison and Stabilitymentioning
confidence: 99%
“…Regarding athlete free swim ability, Ganzevles et al (2019) demonstrated the usefulness of a tri-axial accelerometer for quantifying jerk cost and swimmer smoothness where findings offer insight into refined flow and coordination patterns of elite swimmers. Intra-stroke velocity and intra-cyclic stroke variations measured with inertial measurement units provide promising possibilities into body segment coordination and sequence timing (Worsey et al, 2018).…”
Section: Swim Strokementioning
confidence: 98%